A Case of Chronic Right Hip Pain Revealing an Insidious, Incidental Eight-Centimeter Internal Aneurysm Among Multiple Diffuse Aneurysms - Griffith, Candace (Cureus, 2021)
The prevalence of internal iliac artery aneurysms (IIAA) is very low. Existing data on IIAA are scarce and mainly based on case reports and small retrospective series. We present the case of a 55-year-old African American man with a past medical history of HIV, hypertension, pulmonary embolism (PE), chronic obstructive pulmonary disease (COPD), coronary artery disease, polysubstance abuse, schizophrenia, depression, and bipolar disorder who presented to the emergency department with dyspnea on exertion. He was admitted for COPD exacerbation. He reported concerns of ambulatory chronic right hip pain, for which he underwent a CT, which revealed the presence of a partially visible right IIAA. A CT of his abdomen/pelvis revealed multiple aneurysms, including a partially thrombosed 8-cm fusiform right IIAA. Due to the presence of multiple aneurysms, the vascular surgery team was consulted, and elective repair was recommended. IIAA should be considered in the differential diagnosis of patients with significant smoking history and hip pain and acted upon immediately.